2017
DOI: 10.3390/nu9080834
|View full text |Cite
|
Sign up to set email alerts
|

Soymilk Improves Muscle Weakness in Young Ovariectomized Female Mice

Abstract: Estrogens play a key role in an extensive range of physiological functions in various types of tissues throughout the body in females. We previously showed that estrogen insufficiency caused muscle weakness that could be rescued by estrogen administration in a young female ovariectomized (OVX) mouse model. However, long-term estrogen replacement therapy increases risks of breast cancer and cardiovascular diseases. Soymilk contains plant-based protein and isoflavones that exert estrogen-like activity. Here we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Recent studies demonstrated that ERα is involved in mitochondrial integrity ( Ribas et al., 2016 ), lipid metabolism ( Schweisgut et al., 2017 ), atrophy ( Ogawa et al., 2015 ), and regeneration ( Collins et al., 2019 ) in skeletal muscle. Although E2 preferably binds to ERα, we have found that consecutive intake of soymilk containing isoflavones, which preferentially bind to ERβ, ameliorated muscle atrophy and satellite cell dysfunction in ovariectomized female mice ( Kitajima et al., 2017 ; Kitajima and Ono, 2016 ), suggesting that ERβ signaling is also a factor that regulates both skeletal muscles and satellite cells. However, the roles of ERβ in skeletal muscle and satellite cells are poorly understood.…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies demonstrated that ERα is involved in mitochondrial integrity ( Ribas et al., 2016 ), lipid metabolism ( Schweisgut et al., 2017 ), atrophy ( Ogawa et al., 2015 ), and regeneration ( Collins et al., 2019 ) in skeletal muscle. Although E2 preferably binds to ERα, we have found that consecutive intake of soymilk containing isoflavones, which preferentially bind to ERβ, ameliorated muscle atrophy and satellite cell dysfunction in ovariectomized female mice ( Kitajima et al., 2017 ; Kitajima and Ono, 2016 ), suggesting that ERβ signaling is also a factor that regulates both skeletal muscles and satellite cells. However, the roles of ERβ in skeletal muscle and satellite cells are poorly understood.…”
Section: Introductionmentioning
confidence: 93%
“…In general, ERs and estrogen form dimers and then bind to estrogen receptor binding elements to stimulate target gene transcription and regulate cell proliferation or differentiation [ 42 , 43 ]. ERs are mainly composed of two isoforms, estrogen receptor α (ERα) and estrogen receptor β (ERβ), both of which have been reported to be involved in muscle atrophy [ 44 ], muscle regeneration, and hypertrophy [ 45 , 46 , 47 ]. In this work, it was found that the pro-myogenesis role of NAR was related to ERβ.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, oral intake of natural food sources containing phytoestrogens may be a good alternative. For example, intakes of soymilk containing isoflavones, an active estrogen-like substance, improve muscle weakness in OVX mice ( 152 ). Similar to 17β-estradiol replacement treatment, several investigators found the potential risks associated with androgen therapy ( 153 , 154 ).…”
Section: Mitochondria: a Central Target For 17β-estradiol And Testost...mentioning
confidence: 99%